(untitled) (Architecture Image Studies, 2026)
This study contributes to the field of comparative education by providing unique case analyses. By comparing the education systems of countries that are rarely analyzed together, it enriches scientific knowledge about global educational trends, common patterns, and the characteristics of educational development under different cultural and political conditions.To improve the quality of education, Kyrgyzstan needs to increase investment in educational resources, optimize the allocation of these resources, enhance teacher training, and promote the internationalization and modernization of education.Problems still exist in areas such as the theoretical foundations, research paradigms, and intrinsic motivations of Chinese education. Summarizing and reflecting on the development of the discipline of education requires more longitudinal attention to its contemporary significance, focusing on serving the higher aims of human educational development and contributing Chinese wisdom; in a horizontal sense, it also requires further exploration of its inclusive value and making continuous efforts in building an academic community and enhancing the intrinsic motivation of the discipline.In the end, the comparative approach we adopted opened up new perspectives and enabled us to gain unique insights that could not be obtained by studying each country individually.